POLYMORPHISMS OF SOME GENES, ASSOCIATED WITH HYPERTENSION: A REVIEW OF RELEVANT PUBLICATIONS - V. V. Benberin; G. A. Yermakhanova; N. A. Shanazarov; T. A. Vochshenkova; N. K. Seidalin; N. Y. Lisovska (Scientific Journal of Pedagogy and Economics, 2019)
Purpose of the review: To review relevant publications on the study results of gene polymorphisms in hypertension. Methodology: A search of relevant publications was conducted in electronic databases including Embase, PubMed/Medline, Science Direct, Ebscohost, Springer Link, The Cochrane Library, Web of Knowledge (Thomson Reuters), and eLibrary. The depth of search for publications was 16 years (2002-2018). More than 30 publications were selected and reviewed as analytical material for this article. The inclusion criteria were meta-analyzes, systematic reviews, full-text articles published earlier in 2002, the results of randomized studies, research reports with evidence base. Results and conclusion. An analysis of relevant publications indicated that despite the many ongoing studies on the polymorphisms of genes involved in the renin-angiotensin-aldosterone system in hypertension, the results of these studies are contradictory. Sample size, the specific population and other external factors influence study results. Each population has its own characteristics that affect the result of the study. When assessing the association between gene polymorphisms and the risk of hypertension, it is necessary to take into account changes in the genes with the geographical features of the studied population. In addition, an example of such a study would be the Kazakh population.